2022
DOI: 10.1103/physreve.106.024405
|View full text |Cite
|
Sign up to set email alerts
|

Spiral wave drift under optical feedback in cardiac tissue

Abstract: Spiral waves occur in various types of excitable media and their dynamics determine the spatial excitation patterns. An important type of spiral wave dynamics is drift, as it can control the position of a spiral wave or eliminate a spiral wave by forcing it to the boundary. In theoretical and experimental studies of the Belousov-Zhabotinsky reaction, it was shown that the most direct way to induce the controlled drift of spiral waves is by application of an external electric field. Mathematically such drift oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…in 52 ), many authors have addressed the drift of spiral waves in cardiac tissue in both theoretical 53 and experimental studies 21 . Studies have demonstrated that the drift can be induced by anatomic inhomogeneity 54 , changes in temperature 55 or external electric 56 , 57 , and even optical, stimulation 29 , 58 . Some studies have also demonstrated a putative role of junctional coupling in the dynamics of spiral waves in cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…in 52 ), many authors have addressed the drift of spiral waves in cardiac tissue in both theoretical 53 and experimental studies 21 . Studies have demonstrated that the drift can be induced by anatomic inhomogeneity 54 , changes in temperature 55 or external electric 56 , 57 , and even optical, stimulation 29 , 58 . Some studies have also demonstrated a putative role of junctional coupling in the dynamics of spiral waves in cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for light-induced drift of spiral waves [34,35], chiral changes [36], control of turbulence [37], and other manipulations within myocardial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It is claimed that spirals might undergo parallel and circular drifts. Besides, the frequency of rotation, the chirality, or handedness, [26,42] and curvature [16,43] are critical aspects of a spiral pattern. Hence, one might speculate the given feature might also affect the spirals’ interplay in a multilayer configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several other strategies have been developed, such as electric pulse [20,21], field pacing [22] and recently polarized electric fields [23,24]. Optogenetic manipulation in extended models with photosensitive ion channels [25,26] and feedback-controlled forcing of spiral waves are cutting-edge methods employed to destabilize rotating tips [27]. Given the spatial arrangement of the medium, obstacles of proper size can lead spiral seeds to drift away from the heterogeneous site [28,29].…”
Section: Introductionmentioning
confidence: 99%